His-426 of the Pseudomonas aeruginosa exotoxin A is required for ADP-ribosylation of elongation factor II. - Wozniak, D J (1988)
Exotoxin A (ETA) is recognized as the most toxic product associated with the opportunistic pathogen Pseudomonas aeruginosa. Identification of the amino acids in the polypeptide sequence that are required for toxin activity is critical for vaccine development. By defining the nucleotide sequence of the structural gene of a mutant that encodes an enzymatically inactive ETA (CRM 66), we identified an essential amino acid (His-426), which is involved in the ADP-ribosyltransferase activity associated with functional ETA. A monoclonal antibody that inhibits ETA enzymatic activity in vitro fails to react with ETA variants that have a His 426----Tyr substitution. Several mono-ADP-ribosylating toxins, including diphtheria and pertussis toxins, within the primary amino acid sequences carry a histidine residue that is conserved in spacing and in location with respect to other critical residues. Analysis of the three-dimensional structure of ETA revealed that His-426 is not associated with the proposed NAD+ binding site. These findings should be useful for the design and construction of toxin vaccines.